2009
DOI: 10.1111/j.1472-8206.2009.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the nitric oxide on diazoxide‐induced relaxation of the calf cardiac vein and coronary artery during cooling

Abstract: The effects of cooling (to 28 degrees C) on the vasodilation induced by diazoxide (10(-9)-3 x 10(-4) M) on carbachol-pre-contracted calf cardiac vein and coronary artery and the role of nitric oxide in these effects were analyzed. Diazoxide produced concentration-dependent relaxation of calf cardiac vein and coronary artery rings pre-contracted with carbachol (10(-6) M). During cooling, the pIC(50) values, but not the maximal responses, to diazoxide were significantly lower than at 37 degrees C in both prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Moderate hypothermia, cooling to 25-31°C, has been shown to have a variable influence on the vascular sensitivity to various drugs and endogenous substances in different parts of the vascular system of animals (5). We have previously studied the thermal responses of smooth muscle in various vessels and observed that the sensitivity of different agents were temperature dependent (2,11). Thus, despite current research to determine the effects of temperature on vascular reactivity of different animal species, studies with human tissues remain incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate hypothermia, cooling to 25-31°C, has been shown to have a variable influence on the vascular sensitivity to various drugs and endogenous substances in different parts of the vascular system of animals (5). We have previously studied the thermal responses of smooth muscle in various vessels and observed that the sensitivity of different agents were temperature dependent (2,11). Thus, despite current research to determine the effects of temperature on vascular reactivity of different animal species, studies with human tissues remain incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary venous system (cardiac veins) collects one-third blood of the coronary circulation and is considered to be an important site for the blood-tissue exchange of water and nutrients, as well as a possible determinant of ventricular distensibility. The temperature utilized in this study; 28 °C, for cooling was considered to be "moderate cooling" and 41 °C, "moderate warming" temperature accordingly to previous studies (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Atalik et al [17] reported that cooling (28°C) did not attenuate sodium nitroprusside-induced relaxation in the calf coronary artery and cardiac vein with intact endothelium. Although the reason for this discrepancy is unclear, it seems possible that the coronary artery, but not the aorta, can function in response to NO even under hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Atalik et al [17] investigated the effects of cooling (28°C) on the vasodilation induced by diazoxide on the carbachol-pre-contracted calf coronary artery and cardiac vein. They reported that pIC 50 values, but not maximal responses to diazoxide, were attenuated by cooling.…”
Section: Discussionmentioning
confidence: 99%